PENGGUNAAN RAGAM BAHASA DI RUANG PUBLIK "HOKKY" - Adibah, Wardah Ariij (Journal Analytica Islamica, 2023)
In the current era of globalization, Indonesian faces challenges and problems, especially in its use in public spaces. This study aims to analyze the writing of Indonesian words or sentences in the "Hokky" shopping area. This study uses a qualitative descriptive method with a library study design so that in its implementation it is carried out using inventory techniques, read-see, classify, and record. The data collection technique used comes from publications that are in the shopping area. The results of the study show that the use of Indonesian in the public space where shopping is not satisfactory because there are several errors, such as errors in writing words originating from foreign languages (English and regional) that should be written in print (italic/italic), writing errors between prepositions and prefixes .capital letter writing errors, and writing absorption elements. This research contributes to increasing public awareness about the importance of using Indonesian properly and correctly in public spaces.